EFFECTIVENESS OF USING THINK PAIR SHARE MODEL IN INCREASING STUDENT PARTICIPATION IN ECONOMIC SUBJECTS FROM GENDER PERSPECTIVES - Gunawan, Ariska; Mulyadi, Hari; Istikomah, Navik (Jurnal Pendidikan Ilmu Sosial, 2025)
This study aims to examine the effectiveness of the Think Pair Share (TPS) cooperative learning method in increasing students' participation in Economics subjects and to analyze differences in participation between male and female students. An experimental class taught using the TPS model and a control class taught using traditional methods were part of a quasi-experimental design with a posttest-only control group. Two-Way ANOVA was used to evaluate the data, which were gathered through structured observation of students' participation in class. The results show that the TPS learning model is more effective in improving students’ participation compared to conventional teaching methods. In addition, gender-based disparities in participation were found, with both male and female students benefiting from TPS. These findings highlight the importance of interactive and cooperative learning strategies in fostering active classroom engagement. However, this study is limited by the relatively small sample size and the focus on a single school context, which may restrict the generalizability of the findings. Furthermore, student participation was measured only through observational data without incorporating psychological factors. Therefore, future studies are recommended to involve larger and more diverse samples, apply mixed-method approaches, and include additional variables such as self-efficacy, motivation, and learning interest to obtain a more comprehensive understanding of student participation.